Environmental Regulation of Yersinia Pathophysiology - Chen, Shiyun; Thompson, Karl M.; Francis, Matthew S. (Frontiers in Cellular and Infection Microbiology, 2016)
Hallmarks of Yersinia pathogenesis include the ability to form biofilms on surfaces, the ability to establish close contact with eukaryotic target cells and the ability to hijack eukaryotic cell signaling and take over control of strategic cellular processes. Many of these virulence traits are already well described. However, of equal importance is knowledge of both confined and global regulatory networks that collaborate together to dictate spatial and temporal control of virulence gene expression. This review has the purpose to incorporate historical observations with new discoveries to provide molecular insight into how some of these regulatory mechanisms respond rapidly to environmental flux to govern tight control of virulence gene expression by pathogenic Yersinia.